Effect of computerised cognitive training on cognitive outcomes in mild cognitive impairment: a systematic review and meta-analysis. Issue 8 (18th August 2019) - Zhang, Haifeng; Huntley, Jonathan; Bhome, Rohan; Holmes, Benjamin; Cahill, Jack; Gould, Rebecca L; Wang, Huali; Yu, Xin; Howard, Robert
Abstract : Objectives: To determine the effect of computerised cognitive training (CCT) on improving cognitive function for older adults with mild cognitive impairment (MCI). Design: Systematic review and meta-analysis. Data sources: PubMed, Embase, Web of Science and the Cochrane Library were searched through January 2018. Eligibility criteria: Randomised controlled trials comparing CCT with control conditions in those with MCI aged 55+ were included. Data extraction and synthesis: Two independent reviewers extracted data and assessed the risk of bias. Effect sizes (Hedges' g and 95% CIs) were calculated and random-effects meta-analyses were performed where three or more studies investigated a comparable intervention and outcome. Heterogeneity was quantified using the I 2 statistic. Results: 18 studies met the inclusion criteria and were included in the analyses, involving 690 participants. Meta-analysis revealed small to moderate positive treatment effects compared with control interventions in four domains as follows: global cognitive function (g=0.23, 95% CI 0.03 to 0.44), memory (g=0.30, 95% CI 0.11 to 0.50), working memory (g=0.39, 95% CI 0.12 to 0.66) and executive function (g=0.20, 95% CI −0.03 to 0.43). Statistical significance was reached in all domains apart from executive function. Conclusions: This meta-analysis provides evidence that CCT improves cognitive function in older people with MCI. However, the long-term transfer of these improvements and the potential to reduce dementia prevalence remains unknown. Various methodological issues such as heterogeneity in outcome measures, interventions and MCI symptoms and lack of intention-to-treat analyses limit the quality of the literature and represent areas for future research.